Restoration of early deficiency of axonal guidance signaling by guanxinning injection as a novel therapeutic option for acute ischemic stroke. (March 2021) - Xiao, Guangxu; Lyu, Ming; Li, Zhixiong; Cao, Linghua; Liu, Xinyan; Wang, Yule; He, Shuang; Chen, Zihao; Du, Hongxia; Feng, Yuxin; Wang, Jigang; Zhu, Yan
Graphical abstract: Highlights: First reported that GXNI, a Chinese herbal medicine previously prescribed for coronary artery diseases, had neuroprotective effects on ischemic stroke, which had been verified in vivo and in vitro experiments. Our findings showed that deficiencies in axonal guidance signaling and promoting neurogenesis already occurred in the acute model of stroke. GXNI protected brain tissue from I/R injury via up-regulating SHH-PTCH1-GLI1-mediated axonal guidance signaling to promote axon growth and synaptogenesis. Abstract: Despite of its high morbidity and mortality, there is still a lack of effective treatment for ischemic stroke in part due to our incomplete understanding of molecular mechanisms of its pathogenesis. In this study, we demonstrate that SHH-PTCH1-GLI1-mediated axonal guidance signaling and its related neurogenesis, a central pathway for neuronal development, also plays a critical role in early stage of an acute stroke model. Specifically, in vivo, we evaluated the effect of GXNI on ischemic stroke mice via using the middle cerebral artery embolization model, and found that GXNI significantly alleviated cerebral ischemic reperfusion (I/R) injury by reducing the volume of cerebral infarction, neurological deficit score and cerebral edema, reversing the BBB permeability and histopathological changes. A combined approach of RNA-seq and network pharmacology analysis was used to reveal the underlying mechanisms of GXNI followed by RT-PCR, immunohistochemistry and western blotting validation. It was pointed out that axon guidance signaling pathway played the most prominent role in GXNI action with Shh, Ptch1, and Gli1 genes as the critical contributors in brain protection. In addition, GXNI markedly prevented primary cortical neuron cells from oxygen-glucose deprivation/reoxygenation damage in vitro, and promoted axon growth and synaptogenesis of damaged neurons, which further confirmed the results of in vivo experiments. Moreover, due to the inhibition of the SHH-PTCH1-GLI1 signaling pathway by cyclopropylamine, the effect of GXNI was significantly weakened. Hence, our study provides a novel option for the clinical treatment of acute ischemic stroke by GXNI via SHH-PTCH1-GLI1-mediated axonal guidance signaling, a neuronal development pathway previously considered for after-stroke recovery.